Maxillary Sinus Mucocele as a Late Complication in Zygomatic-Orbital Complex Fracture - Silva de Menezes, Juliana Dreyer da [UNESP]; Moura, Lucas Borin [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Thieme Medical Publ Inc, 2016)
This article presents an unusual case of maxillary sinus mucocele as a late complication of zygomatic-orbital complex fracture, 23 years after the initial treatment. The patient was referring diplopia and decreased visual acuity with signs of dystopia, proptosis, and epiphora. Computed tomographic scan revealed an expansive lesion in the maxillary sinus with surrounding bone erosion and displacement of the eyeball. Treatment option was excisional biopsy and orbital floor reconstruction with titanium mesh restoring the appropriate orbital position. We propose that in the case of postoperative ophthalmological sequelae of facial fractures involving paranasal sinuses, mucocele should be considered in the differential diagnosis.
Keywords: mucocele; maxillary sinus; proptosis